Plight of HIV infected women : plan of action for prevention and control - Sakthi, S. (New Delhi : Discovery Pub. House, 2010)
With reference to Chennai city, India.
Includes bibliographical references (p. [298]-317)
Keywords: HIV-positive women -- India -- Madras -- Social conditions; AIDS (Disease) in women -- India -- Madras -- Social conditions; AIDS (Disease) -- India -- Madras -- Prevention; HIV infections -- India -- Madras -- Prevention